PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN MOTIVASI BELAJAR DI SMP ISLAM AL-WASI MAROS - Nurlaela; Bunyamin, Andi; Syahrul, Muhammad; Surani; Subaedah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of Augmented Reality (AR)-based interactive learning media to enhance student learning motivation in the Islamic Religious Education subject for Grade VIII students at SMP Islam Al-Wasi Maros. The study employed the Classroom Action Research (CAR) method, conducted over two cycles, with each cycle comprising the stages of planning, implementation, observation, and reflection. The research subjects consisted of 32 Grade VIII students. Data collection techniques included observation, learning motivation questionnaires, documentation, and learning evaluations. The results indicate that prior to the implementation of AR media, student learning motivation fell into the "very low" category, with an average score of 57.81. Following the implementation of AR-based interactive learning media in Cycle I, the average learning motivation score rose to 77.50, placing it in the "sufficient" category. Subsequently, after instructional improvements were made in Cycle II, the average learning motivation score increased to 84.81, falling into the "good" category. Observations also revealed increased student engagement in the learning process, evidenced by attention to the material, active questioning and discussion, the confidence to express opinions, enthusiasm, task completion ability, and participation in learning activities. In Cycle II, 26 students (81.25%) fell into the "good" and "very good" categories. Furthermore, learning evaluation results showed an average score of 85.34, with 31 students (96.88%) meeting the Minimum Mastery Criteria (KKM). Thus, the implementation of Augmented Reality-based interactive learning media can enhance student learning motivation in the Islamic Religious Education subject for Grade VIII students at SMP Islam Al-Wasi Maros.